DISRUPSI FINANCIAL TECHNOLOGY (FINTECH) DI INDONESIA (Jurnal Riset Akuntansi, 2022)
The purpose of this study is to understand the FinTech ecosystem in Indonesia and to understand the disruption of FinTech innovation in Indonesia. The research method is carried out through qualitative methods with an explorative descriptive approach. The data processed in this study are secondary data and a literature review on Fintech and Disruptive Innovation. Data collection is carried out through a review of the FinTech literature, identifying Fintech companies operating in Indonesia, collecting data from sources (websites, financial industry articles, world bank reports, Bank Indonesia reports, OJK reports). This research focuses on content analysis of secondary data, which refers to a systematic and replicable technique for compressing large amounts of text into fewer content categories. The research results show that the FinTech ecosystem in Indonesia is experiencing rapid growth by offering 8 (eight) product categories, of which the Lending category is the most prominent area, and has won the second position in the top two funding positions after Singapore at the ASEAN level. The results of the study also found elements of disruptive innovation and others maintaining innovation in the category of FinTech companies in Indonesia. The solution offered based on the results of this research is that entrepreneurs in the FinTech sector can understand the purpose of innovation disruption to be able to face challenges as well as take advantage of opportunities to move forward because innovation disruption is considered a means of business growth and development. Keywords: FinTech, Inovation Disruption